INTERMETALIC PHASES STUDY IN THE PROCESS OF DISSIMILAR WELDING OF ALUMINIUM TO STEEL - Andrian Nababan, Kevin
Technological improvement and regulation always demand of improvement on the design, light and strong structure, and low carbon emission, leading to the attempt of joining aluminium to steel. This kind of structure is needed in automotive, aviation and shipbuilding industry. Joining aluminium to steel is challenging due to their incompatible thermo-physical properties, leading to problems such as formation of hard and brittle layer at the interface composed of Fe-Al intermetallic phases, pores in fusion zone, and formation of zinc rich zone, etc. Previous studies said that intermetallic phases (Fe2Al5) is problematic because of uncontrolable growth governed by the structural defect, i.e ~30% vacancies along the long axis which facilitates the diffusion of Al atoms, however the growth of intermetallic phases (Fe2Al5) is not yet comprehensively understood. First of all, collection of published research papers, containing key words: dissimilar welding, intermetallic copounds, fller composition, brazing is conducted. Second, elimination of irrelevant research results is undertaken. Third, an analysis of the collected research papers is done in regard to answer research objectives. Fourth, comparison of research resultsm finding unanswered questions from other sourcesm are done. Fifth, conclusion is derived from the conducted critical review. This study highlight key challenges during joining Al to Steel and discusses methods to improve the joint properties primarily by suppresing the formation of intermetallic compounds, composition of filler wire, and the most suitable welding method. In addition, role of Silicon and Zinc is reviewd systematically. This study found that the most suitable technique used in hybrid spot joining and hybrid lap welding is Friction Stir Welding, and explain intermetallic phase growth mechanism in the interdifussion of Fe-Al, and also explain about the role of Silicon and Zinc in the process of dissimilar welding of aluminium and steel. Further study to analyze role of base material composition, influence of coating thickness on the interface reaction, and influence of cross tension test on the joint.